2015
DOI: 10.1080/00140139.2015.1076059
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the structure of non-routine decision processes in Airline Operations Control

Abstract: ControlUnfamiliar severe disruptions challenge airline operations control professionals most, as their expertise is stretched to its limits. This study has elicited the structure of airline operations control professionals' decision process during unfamiliar disruptions by mapping three macrocognitive activities on the decision ladder: sensemaking, option evaluation, and action planning. The relationship between this structure and decision quality was measured. A simulated task was staged, based on which think… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…The types of rule which emerged from this post-hoc reflection generates powerful tools for the future. Certainly, the use of rule-based strategies has been shown as a good way to handle unexpected or novel challenges (Richters et al, 2015 ). In this case it is interesting to see the ways in which rules may have emerged from initially intuitive action.…”
Section: Resultsmentioning
confidence: 99%
“…The types of rule which emerged from this post-hoc reflection generates powerful tools for the future. Certainly, the use of rule-based strategies has been shown as a good way to handle unexpected or novel challenges (Richters et al, 2015 ). In this case it is interesting to see the ways in which rules may have emerged from initially intuitive action.…”
Section: Resultsmentioning
confidence: 99%
“…Flight disruptions can either cause almost negligible consequences or they can escalate very quickly, propagating across the flight network and impairing the airline’s ability to operate scheduled flights on time and to maintain the continuity of operations (Kohl et al, 2007; Richters et al, 2016). Airlines operate in a dynamic and competitive environment, with narrow financial margins and reduced slack, balancing efficiency and the ability to recover from disruptions (Abdelghany et al, 2004; Castro & Oliveira, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have advanced the understanding of the decision-making processes inside OCCs as naturalistic (Gore et al, 2015; Klein, 2008, 2015) rather than rational and are mainly based on the expertise of Operations Controllers, especially when troubleshooting flight disruptions (Bruce, 2011; Bruce & Gray, 2004, 2019; Feigh & Pritchett, 2007; Igbo, 2013; Richters et al, 2016). Some of these studies observe that these controllers rely heavily on their background experience and contextual situations, using scenarios experienced in previous disruptions and negotiating the rules to implement complex strategies rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning specific characteristics of work situations related to decision making, previous studies suggested that it is important to distinguish between routine and non-routine situations (e.g., Betsch et al, 2002;Richters et al, 2016;Sedlár, 2016). While routine situations are usually characterized by high level of certainty, self-confidence and application of decision making procedures, which rely on a particular option activated by a situation, non-routine situation involves high level of uncertainty, disruption of standard procedures and application of decision making strategies based on the reframing of an unfamiliar situation (Richters et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While routine situations are usually characterized by high level of certainty, self-confidence and application of decision making procedures, which rely on a particular option activated by a situation, non-routine situation involves high level of uncertainty, disruption of standard procedures and application of decision making strategies based on the reframing of an unfamiliar situation (Richters et al, 2016). In many non-routine situations, especially in a work setting, wrong decisions can have negative consequences (Richters et al, 2016). Such consequences can lead to experience of negative emotions such as anxiety, worry, etc., and can influence the cognitive processes underlying decision making (Baumann et al, 2001).…”
Section: Introductionmentioning
confidence: 99%